Novel electrochemical sensing platform based on a nanocomposite of PVA / PVP / RGO applied to IgG anti- Toxoplasma gondii antibodies quantitation - Takara, Eduardo Andres (2019)
This article describes the development of a new electrochemical platform composed by a polymer mixture and graphene oxide (GO). The working electrode of a screen-printed carbon electrode (SPCE) was modified with nanocomposite constituted by poly-vinyl alcohol (PVA), poly-vinylpyrrolidone (PVP) and GO, which was electrochemically reduced to obtain PVA/PVP/RGO/SPCE. The interactions and morphology of the PVA/PVP/GO nanocomposite were investigated by SEM, FTIR and UV-Vis. SEM images indicated an excellent dispersion of the GO sheets in the polymer matrix. Besides, FTIR and visible UV studies revealed strong interactions between polymer mixture and GO sheets. According to electrochemical studies, the new platform increased the electroactive surface area by a factor of 20.46 compared to the unmodified SPCE. Also, the PVA/PVP/RGO/SPCE had a fast electron kinetics transfer process with a value of ks = 9.6 s-1.The modified electrode was applied to the determination of IgG anti-T. gondii antibodies for the serological diagnosis of toxoplasmosis. The IgG anti-T. gondii antibodies quantification showed a detection limit of 0.012 U mL-1, and the coefficients of variation intra-day and inter-day assays were lower than 4.5% and 6.2%, respectively. The electrochemical platform proved to be a sensitive and easily applicable tool applied to the serological diagnosis of toxoplasmosis. Therefore, the developed nanocomposite represents an excellent alternative for the electrochemical biosensor fabrication.